Ethics in Consumer Choice: The Influence of Ethical Issues on Nottingham University Students’ Apparel Purchase Decision - Meng, Zijun (2009)
This paper attempts to examine Nottingham university students’ attitude towards ethical fashion and ethical consumption in general. A large amount of journal article were consulted and used as theoretical foundation to support and develop primary research. A triangulated research methodology which involves 150 questionnaire survey and 4 face to face interviews have been carried out. The primary research finding suggest students are unlikely to make a socially responsible decision if they have to make tradeoffs between non-economic criteria and personal interests such as paying a premium price, fashion desire.